Anti-CD20 monoclonal antibody (rituximab) treatment for cryoglobulinemic vasculitis: where do we stand?. Issue 3 (20th July 2007) - Cacoub, P; Delluc, A; Saadoun, D; Landau, D A; Sene, D
Abstract : Mixed cryoglobulinemia (MC) vasculitis represents a complication of the B cell response to a variety of chronic inflammatory diseases. Recent reports describe the use of monoclonal antibodies directed to CD20 antigen (rituximab), a transmembrane protein expressed on pre-B lymphocytes and mature lymphocytes. The goal of this article is therefore to review published data in order to better analyse the efficacy and tolerance of rituximab treatment in patients with MC vasculitis. After systematic review of the literature and exclusion of review papers, 13 manuscripts were identified that reported on a total number of 57 cases of MC secondary to hepatitis C virus (HCV) infection (75.4%) or essential mixed cryoglobulinemia (24.6%). Previous treatments failed to control the main signs of vasculitis; these were either HCV (n = 37) or immunomodulating treatments. Most patients (48 out of 57) received four weekly consecutive intravenous infusions of 375 mg/m 2 of rituximab. The duration of follow-up after rituximab therapy was 9.7 months. Rituximab infusions had great efficacy on the main vasculitis signs, with a clinical response in 80–93% patients. A relapse of MC was noted in 14 out of 36 (39%) patients. A relatively small number of side effects were reported. We conclude that rituximab therapy for patients with mixed cryoglobulinemia vasculitis, HCV-induced or essential, shows great efficacy on the main vasculitis signs in the majority of reported patients. A relapse of cryoglobulinemia vasculitis was frequently noted. Randomised controlled trials with long-term study are needed to form definitive conclusions on the benefit/risk ratio of rituximab therapy in such patients.